A Study on Financial Product Knowledge, Attitudes and Behaviours Among Malaysian Young Working Adults - Lim, Sze Ying; Amer Azlan Abdul Jamal (Secholian Publication (Kuala Lumpur, Malaysia), 2023)
The purpose of this study is to assess the level of financial products knowledge and its relation with financial attitude and behaviour among young working adults in Malaysia. A self-administered and structured online survey method was applied involving a total of 384 respondents using the non-probability convenience sampling technique. Data was evaluated and analysed using Statistical Package for the Social Science (SPSS v.28) software. The findings show that most respondents possessed good level of financial products knowledge particularly on questions pertaining to savings and insurance products, whilst questions on credit card were deemed to be slightly difficult. Apart from that, most respondents perceived to have good attitude on having life insurance for family protection, and also think that they are able to control current and future financial situation. From the perspective of financial behaviour, most respondents perceived to compare prices before buying, prepare a budget for spending and track their spending pattern. However, maintaining an adequate financial records and doing regular savings were the least behaviours that they would practice.